A Systematic Review on Artificial Intelligence (AI) Assisted Drug and Vaccine Development against SARS-CoV-2 - Singha, Vishal; Ghosh, Suvendu; Singha, Partha Sarathi; Datta, Sutapa; Ghosh, Debosree (Coronaviruses, 2025)
BackgroundAdaptation and application of Artificial Intelligence (AI) technology for the development of drugs against the deadly and continuously mutating Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has been extremely beneficial, cost-effective, and time saving for the scientific community. A systematic review is necessary for complete picturization of the overall AI assistance in developing drugs and vaccines against SARS-CoV-2.Materials and MethodsA systematic analysis and review of the research literature available on the application of AI in the development of drugs and vaccines against SARS-CoV-2 from various online platforms like Web of Science, PubMed Central, Science Direct, ResearchGate, Scopus, Google Scholar, Medline, Embase etc., has been performed, and relevant full papers have been selected on certain selection criteria and have been used for this review.ResultsUtilization of AI tools has enabled the selection, modification, evaluation, and prediction of the effectiveness of drug formulations against coronavirus disease (COVID-19) in a very rapid and efficient manner. Vaccine development against the deadly SARS-CoV-2 has also been aided and benefited immensely by using AI tools and technique.DiscussionThousands of studies regarding the development of effective drugs and vaccines against the constantly evolving, mutating, and prevailing SARS-CoV-2 have been conducted, and several thousands are still being conducted around the world.ConclusionAI is a powerful tool, and its application has been highly beneficial in developing effective drugs and vaccines against the deadly SARS-CoV-2 in a cost-effective and time-effective frame. This systematic review briefs the findings and achievements till the date of writing this article in the field of AI-assisted drug and vaccine development against COVID-19.
Keywords: SARS-CoV-2